Chitosan-laponite nanocomposite scaffolds for wound dressing application - Gonzaga, Virginia de A. M. (2019)
The pivotal issue of skin regeneration research is the development of effective biomaterials that exhibit biological activities as fungicide and bactericide, combining simple and low cost manufacturing technologies. In this context, nanocomposite scaffolds based on chitosan (Ch)/Laponite (Lap) were produced by using different concentrations of Lap via freeze-drying process for potential application in skin regeneration. The influence of Lap concentration on the scaffold properties was evaluated. The prepared scaffolds were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), porosity, swelling capacity, and mechanical analyses. The results revealed that the scaffolds exhibited a porous architecture, besides the increase in the clay content, leads to an increase in the porosity, an improvement of mechanical strength, and a decrease of swelling capacity. In vitro tests were also carried out to evaluate the biocompatibility of the materials, such as bioadhesion, antibacterial activity, viability, and cell adhesion. Viability and cell adhesion demonstrated that all scaffolds were not cytotoxic and the fibroblast cells readily attached on the surface of the scaffolds. Thereby, the results suggested that the nanocomposite scaffolds are biomaterials potentially useful as wound dressings.